Evaluating the paleomagnetic reliability in fold and thrust belt studies - Pueyo, E. L. (TRABAJOS DE GEOLOGÍA, 2010)
Paleomagnetic data are essential for a real 3D understanding of fold and thrust belts and area unique kinematic indicator to help understand the processes of lateral transference of deformation.In association with the bedding surface it is one of the very few natural indicators able to unambiguouslyrelate the deformed and undeformed stages. However, paleomagnetic data are sometimes misinterpretedor ignored. An analysis of the implicit assumptions in paleomagnetic studies of fold andthrust belts reveals three possible sources of error with an intrinsic structural (geometric) control; 1)overlapped paleomagnetic directions (laboratory isolation failures), 2) rock volume deformation passivelyrecorded by the paleomagnetic vector (non rigid-body behaviour), and 3) incorrect restorationof beds in non-coaxial structures (bedding correction failures in conical, plunging folds, etc). The differenterrors can be detected by applying simple geometric techniques like the stereographic scattering,the inclination vs. dip and the declination vs. strike diagrams, the fold test, the small circle reconstructionduring unfolding and the geometry of the dispersion of the net tectonic rotation axes. Finally, alist of reliability criteria is proposed to evaluate the quality of investigation focused on the characterizationof vertical axis rotations in fold and thrust belts.